QUALITY LEARNING THROUGH COOPERATIVE LEARNING MODEL BASED ON CASES - Muhammad Nurhusain (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
This study aims to improve the quality of mathematics learning which includes process quality and learning outcomes through case-based cooperative learning model. The type of research is classroom action research with subject of student of class VII.2 MTs.S Ujung Jampea counted 19 people. The results of research related to quality of learning include process quality and quality of results. (1) The quality of the process shows improvement, namely: (a) Student Activity of Cycle I, there are still some aspects of student activity in active enough category so it still needs to be improved / improved. While Cycle II, all aspects of student activity have been at least in the category of active so that can be maintained. (B) The ability of teachers to manage Cycle I learning, there are still some aspects of the ability of teachers to manage learning, are in good enough category that still needs to be improved / improved. While Cycle II, all aspects of the ability of teachers to manage the minimal learning has been in the good category so it can be maintained. (C) Student response cycle I, as much as 78.95% who gave a positive response. While Cycle II, as many as 89.47% which gives positive response. (2) The quality of learning result shows that: (a) Cycle I, the average score of student learning outcomes is 75.1579 with the standard deviation of 9.5699. While Cycle II, the average score of students is 80.8421 with a standard deviation of 6.13064. (B) Classical completeness of Cycle I, students who complete the study individually as many as 12 people or 63.16%. While Cycle II, students who complete the study individually as many as 17 people or 89.47%. Based on the quality of process and learning outcomes can be concluded that the implementation of cooperative learning model based case can improve the quality of learning in students of class VII.2 MTsS Ujung Jampea